2004
DOI: 10.1111/j.1524-4725.2004.30307.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Tumors in Patients Aged 90 Years and Older

Abstract: Dermatologists often attend patients aged 90 years or over with nonmelanoma skin cancer. The most important decision is as to what is the best management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
2
18
0
5
Order By: Relevance
“…The combination of these two factors results in an increase in the number of elderly patients with NMSC currently seen in dermatologic clinics, and a predicted increase in years to come. Moreover, there is virtually no research in dermatology that specifically targets adults over the age of 65, 10 and these patients are being handled in a disjointed way by different dermatologists. 6 The skin of elderly patients is both functionally and structurally different from that of younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these two factors results in an increase in the number of elderly patients with NMSC currently seen in dermatologic clinics, and a predicted increase in years to come. Moreover, there is virtually no research in dermatology that specifically targets adults over the age of 65, 10 and these patients are being handled in a disjointed way by different dermatologists. 6 The skin of elderly patients is both functionally and structurally different from that of younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although there may always be the occasional very elderly patient with multiple comorbid medical conditions whose skin cancer can be more easily handled with simple electrodesiccation and curettage, Mohs surgery does appear to be a safe and effective therapy for the great majority of very elderly patients in the USA [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…The BCC/SCC ratio in our material was 3.5 and is similar to the observation by MacFarlane et al [10] (3.2). Pascual et al [11] in a retrospective analysis of 52 patients over 90 years old showed SCC in 27.8% of patients (BCC/SCC ratio 1.8). In a Tunisian study the BCC/SCC ratio was almost 3, but the analysis was based on patients over 65 years old [12].…”
Section: Discussionmentioning
confidence: 99%